Sources and manifestations of foreign language anxiety - Petrić Kruna; Milivojević Vesna; Moretić-Mićić Snežana (Trendovi u Poslovanju, 2021)
Foreign language anxiety (FLA) is a type of anxiety related to all situations in which an individual is learning a foreign language. Are language teachers and learners in Serbia familiar with foreign language anxiety? If yes, to what degree? If no, why not? The problem needs to be recognized and acknowledged in order to be solved. FLA encompasses many a things, including personal traits, motivation, affect, age, the all important extroversion / introversion dichotomy, why it is happening and how, and what we can do about it, etc. In this paper, the goal is to explain the main sources and manifestations of FLA and, hopefully, raise a few questions for further discussion. If one wants to tackle the problem of FLA and try to help students overcome it, one must know where FLA comes from and how to recognize it in the classroom. This paper is not intended only for teachers, but also for students who have maybe thought about it but did not know it has a name - foreign language anxiety - and that there are ways to mitigate it.